Reducing complexity of patient decision aids for community-based older adults with dementia and their caregivers: multiple case study of Decision Boxes. Issue 5 (9th May 2019) - Bilodeau, Gabriel; Witteman, Holly; Légaré, France; Lafontaine-Bruneau, Juliette; Voyer, Philippe; Kröger, Edeltraut; Tremblay, Marie-Claude; Giguere, Anik M C
Abstract : Objectives: To identify patient decision aids' features to limit their complexity for older adults with dementia and their family caregivers. Design: Mixed method, multiple case study within a user-centred design (UCD) approach. Setting: Community-based healthcare in the province of Quebec in Canada. Participants: 23 older persons (aged 65+ years) with dementia and their 27 family caregivers. Results: During three UCD evaluation-modification rounds, participants identified strengths and weaknesses of the patient decision aids' content and visual design that influenced their complexity. Weaknesses of content included a lack of understanding of the decision aids' purpose and target audience, missing information, irrelevant content and issues with terminology and sentence structure. Weaknesses of visual design included critics about the decision aids' general layout (density, length, navigation) and their lack of pictures. In response, the design team implemented a series of practical features and design strategies, comprising: a clear expression of the patient decision aids' purpose through simple text, picture and personal stories; systematic and frequent use of pictograms illustrating key points and helping structure patient decision aids' general layout; a glossary; removal of scientific references from the main document; personal stories to clarify more difficult concepts; a contact section to facilitate implementation of the selected option; GRADE ratings to convey the quality of the evidence; a values clarification exercise formatted as a checklist and presented at the beginning of the document to streamline navigation; involvement of a panel of patient/caregiver partners to guide expression of patient priorities; editing of the text to a sixth grade reading level; UCD process to optimise comprehensiveness and relevance of content and training of patients/caregivers in shared decision-making. Conclusions: The revised template for patient decision aids is designed to meet the needs of adults living with dementia and their caregivers better, which may translate into fewer evaluation-modification rounds.